Effect of 2-hexanol and methanol on the one-pot process of dehydration and alkoxycarbonylation for the synthesis of esters - N. T. Sevostyanova; S. A. Batashev; A. S. Rodionova; D. K. Kozlenko (Тонкие химические технологии, 2024)
Objectives. To study the possibility of one-pot synthesis (combination of two processes in one reactor) for the following pairs of processes: (1) dehydration of 2-hexanol and isomerizing alkoxycarbonylation of the resulting 2-hexene, in order to obtain 2-hexyl heptanoate, and (2) dehydration of 2-hexanol and isomerizing methoxycarbonylation of the resulting 2-hexene, in order to obtain methyl esters of C7 carboxylic acids. To investigate the effect of the concentrations of 2-hexanol and methanol on the rate of the one-pot synthesis.Methods. One-pot synthesis was studied in a toluene medium in a steel batch reactor designed to operate at elevated pressure and equipped with a glass insert, a magnetic stirrer, a sampler, and gas input and discharge devices. Samples of the reaction mass were taken during the combined process and were analyzed by means of gas–liquid chromatography with a flame ionization detector.Results. The possibility of one-pot combination was demonstrated for 2-hexanol dehydration catalyzed by methanesulfonic acid, as well as for the isomerizing alkoxycarbonylation of the resulting 2-hexene with 2-hexanol and CO, catalyzed by the Pd(PPh3)2Cl2–XANTPHOS–methanesulfonic acid system. The dependencies of the rates of the dehydration of 2-hexanol and the formation of esters of C7 carboxylic acids on the concentration of 2-hexanol were shown to pass through a maximum. The possibility of the one-pot process was proved for the synthesis of esters from 2-hexanol, methanol, and CO with the predominant formation of heptanoic acid esters in the presence of the above catalytic system. The rates of dehydration of 2-hexanol and the formation of 2-hexyl esters of C7 carboxylic acids were found to decrease with increasing the concentration of methanol in the reaction mass. Under mild conditions (temperature 115°C, CO pressure 3 MPa) with the addition of methanol, the total fraction of 2-hexyl and methyl heptanoic acid esters among C7 carboxylic acid esters was determined to be 85.5%.Conclusions. The reactions of intramolecular acid–catalytic dehydration of 2-hexanol and isomerizing alkoxycarbonylation of the resulting 2-hexene, catalyzed by the Pd(PPh3)2Cl2–XANTPHOS–methanesulfonic acid system, can be performed as a one-pot process. Methanesulfonic acid simultaneously functions as a catalyst for the dehydration of 2-hexanol and a cocatalyst for the palladium–phosphine system for the alkoxycarbonylation of hexenes. In the presence of the Pd(PPh3) 2Cl2–XANTPHOS–methanesulfonic acid catalytic system, processes for the synthesis of heptanoic acid esters from 2-hexanol, methanol, and CO can be combined within one reactor. An increase in the methanol concentration negatively affects the rate of the dehydration of 2-hexanol and the formation of 2-hexyl esters of C7 carboxylic acids. A small amount of methanol in the reaction mass leads to an increase in the fraction of heptanoic acid esters among C7 carboxylic acid esters.